Psikoedukasi konsep diri positif pada remaja di Surabaya - Evelyna, Illene; Aulia’ul Haque, Sayidah (Abdimas Siliwangi, 2025)
Adolescence is an important phase in identity formation, including building a positive self-concept. A healthy self-concept is an important foundation for adolescents’ psychological and social well-being. This study aims to improve adolescents’ understanding of positive self-concept through psychoeducation activities. The activity was carried out in one of the junior high schools in Surabaya with a total number of participants of 23 seventh grade students. The methods used included the provision of psychoeducative materials, interactive discussions, and evaluation through pre-test and post-test. Data were analyzed using the Shapiro-Wilk normality test and t-test. The test results showed that the data were normally distributed (p> 0.05) and there was a significant increase in student understanding after participating in psychoeducation (p = 0.000). The average score increased from 36 to 82. These results indicate that psychoeducation is effective in increasing students’ understanding of positive self-concept. Psychoeducation also had a positive impact on students' motivation to understand and apply a healthy self-concept in their daily lives. Therefore, this program can be recommended as one of the preventive interventions in supporting adolescent mental health in the school environment.